EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON GROWTH PARAMETERS OF BIRD OF PARADISE [ ARADISE [STRELITZIA REGINAE REGINAE REGINAE (L.)] - YATHINDRA, H. A.; MANOHAR, R.KRISHNA; RAJESH, A. M. (The Bioscan, 2016)
A research to know the effect of Integrated Nutrient Management (INM) on growth parameters of Bird of Paradise [Strelitzia reginae (L.)]” was conducted at Horticulture Research Station (HRS), University of Agricultural Sciences, GKVK, Bangalore during 2010-2012. One-year-old Bird-of-Paradise plants were supplied with different combinations of organic and inorganic nutrient sources. Spacing of 1.5m X 1.5m was maintained and laid out in Factorial Randomized Complete Block Design with three replications. Among the growth parameters, significantly highest plant height (117.72 cm), maximum leaf length (36.96cm), leaf width (16.14cm), number of leaves (75.77), number of suckers (13.88) and plant spread (9787 cm2) were recorded in plants receiving 80 per cent RDF through fertigation plus organic source of nutrients like Vermicompost (300g) along with different biofertilizers such as Azotobacter, PSB and KMB (T11), whereas least observations were recorded (73.93 cm, 29.68cm, 10.94cm, 34.33, 5.22 and 3361.67cm2 respectively) in plants received 100 per cent RDF as normal fertilizers through soil application (T1 ). These results clearly indicate the beneficial effect over the conventional method of nutrition management and also suggest that combined application of inorganic fertilizers, biofertilizers and vermicompost was superior over their individual application for better plant growth and development.